2019
DOI: 10.1080/20002297.2019.1647036
|View full text |Cite
|
Sign up to set email alerts
|

Toothbrushes may convey bacteria to the cystic fibrosis lower airways

Abstract: Recent findings indicate that the oral cavity acts as a bacterial reservoir and might contribute to the transmission of bacteria to the lower airways. Control of a potentially pathogenic microbiota might contribute to prevent the establishment of chronic infection in cystic fibrosis. We evaluated the presence of CF microorganisms in saliva and toothbrushes of CF patients and verify their possible transmission to lower airways. Methods: We assessed the presence of P. aeruginosa, S. aureus, S. maltophilia, A. xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Importantly, this study also demonstrated that P. aeruginosa genotyping showed two identical clones on the patients' toothbrushes and in their sputum 6 . More recently, an Italian study demonstrated that in 31 patients, these patients had contemporary the same species in sputum and saliva/toothbrush, and in most cases, the clonal identity of the strains among the different sites was confirmed 7 . Both studies concluded that effective toothbrush decontamination methods need to be developed to prevent CF lung infections.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Importantly, this study also demonstrated that P. aeruginosa genotyping showed two identical clones on the patients' toothbrushes and in their sputum 6 . More recently, an Italian study demonstrated that in 31 patients, these patients had contemporary the same species in sputum and saliva/toothbrush, and in most cases, the clonal identity of the strains among the different sites was confirmed 7 . Both studies concluded that effective toothbrush decontamination methods need to be developed to prevent CF lung infections.…”
Section: Introductionsupporting
confidence: 53%
“…aureus was detected in 22%, 13%, and 13% of these groups, respectively 6 . In a recent study from Italy, these pathogens were also detected in toothbrushes from patients with CF, where the authors highlight the potential role of toothbrushes as a source of oral contamination, postulating their role as a reservoir and conduit of pathogens from the environment, via the oral cavity, to the lower airways 7 . Furthermore, both studies demonstrated the presence of similar clonal types of organism found on a toothbrush and in the same patient's sputum/lower airways 6,7 …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Cystic fibrosis (CF) is a life-limiting, multisystem autosomal recessive genetic disorder with a wide range of clinical and genetic variants [ 1 ]. CF most commonly affects Caucasians, with 70,000 people diagnosed worldwide [ 2 ]. It is caused by gene mutations in the CF transmembrane conductance regulator (CFTR) on the long arm of chromosome 7 that contributes to an abnormal chloride and sodium transportation across the epithelial cell membrane.…”
Section: Introductionmentioning
confidence: 99%